Isolation, in vitro Evaluation, and Molecular Docking Analysis of a Bioactive Phenylpropanoid from Syzygium jambos with Antioxidant and Anticancer Potential against IMR-32 Neuroblastoma Cells - Shanth, P. (Asian Journal of Pharmaceutics (AJP), 2025)
Neuroblastoma is a highly aggressive pediatric cancer with limited treatment options and a meager prognosis in advanced stages. Plant-derived natural products represent a valuable source of novel anticancer agents. Syzygium jambos (L.) Alston, traditionally used in folk medicine, has been reported to contain bioactive phenolics, but its anticancer potential remains underexplored. Objective: This study aimed to isolate and characterize bioactive compounds from S. jambos leaves and evaluate their cytotoxic potential against human neuroblastoma infant mortality rat (IMR)-32 cells. Materials and Methods: Leaves of S. jambos were sequentially extracted with solvents of increasing polarity, and extracts were screened for antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The ethanol extract, which showed the highest radical scavenging activity, was subjected to bioassay-guided fractionation by Thin- layer chromatography and silica gel column chromatography. Fractions were tested for antioxidant and cytotoxic activity, and the most active fraction was structurally characterized by spectroscopic and chromatographic methods. Cytotoxicity against IMR-32 cells was evaluated by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay, intracellular reactive oxygen species (ROS) levels were measured, and Western Blotting was used to assess apoptosis- and survival-related proteins. In silico molecular docking and ADME analysis were performed to explore the mechanism and drug-likeness. Results: The ethanol extract of S. jambos leaves showed strong antioxidant activity, with Syzygium jambos Ethanol fracion (SJEF-16) exhibiting 75.25% DPPH inhibition at 500 μg/mL and an IC50 of 40.93 μg/ mL. SJEF-16 decreased IMR-32 neuroblastoma cell viability in a dose-dependent manner, with an IC50 of 28.92 μg/ mL, reduced intracellular ROS levels, and moderately downregulated EGFR expression (66.2% of control). Molecular docking revealed a binding affinity of −6.2 kcal/mol with neuroblastoma-related targets, and ADME analysis predicted good oral bioavailability (bioavailability score = 0.55). These findings suggest SJEF-16 as a promising antioxidant and anticancer agent. Conclusion: This study reports, for the 1st time, the isolation of (2E)-3-(3-Methoxyphenyl)-2-propen- 1-ol from S. jambos leaves with potent cytotoxic and antioxidant activity against neuroblastoma cells. These findings highlight its potential as a promising lead compound for the development of plant-derived therapeutics against pediatric neuroblastoma